Implementasi Sistem Interkoneksi Basis Data Terdistribusi Menggunakan Socket API - Yulianto, Ary (Jurnal Komtika, 2017)
Majelis Pendidikan Dasar dan Menengah Pimpinan Daerah Kabupaten Magelang needs information about the development of the school. The necessary data include data on human resources, asset data and data of their students. At the moment the data is obtained manually by looking to the schools. With the development of information technology is now expected to have a school information system that can provide information quickly and accurately. Data on each school if put into one large server or big data can be used to analyze the data. The purpose of this research is to implement the interconnection of distributed database system using the socket API. It is used to provide master data of all schools under Persyarikatan Muhammadiyah. To support the analysis of the data interconnection of distributed databases, socket API technology is used. With a system like this then the communications database can be connected so that the schools data will be sent directly through the socket API and the data will automatically be processed by the webservice in the server middleware and will be utilized in the next process.